Studies on adhesive behavior of incompatible rubbers - V. Ya. Kiselev (Тонкие химические технологии, 2006)
By the example of incompatible rubbers compositions were investigated adhesive characteristic blend substance to adhesive from one of the components. Were shown, that nonpolar rubber mainly presents at the blanket; result in non-additivity of plybond strength and adhesion moistening functioning. As a result of non-polar rubber molecules orientation at the blend, adhesive properties decrease compare with the autogesion characteristics.